The dual nature of the nucleolus - Tartakoff, Alan; DiMario, Patrick; Hurt, Ed; McStay, Brian; Panse, Vikram Govind; Tollervey, David (Genes & development, 2022)
The nucleolus is best known for housing the highly ordered assembly line that produces ribosomal subunits. The >100 ribosome assembly factors in the nucleolus are thought to cycle between two states: an operative state (when integrated into subunit assembly intermediates) and a latent state (upon release from intermediates). Although it has become commonplace to refer to the nucleolus as “being a multilayered condensate,” and this may be accurate for latent factors, there is little reason to think that such assertions pertain to the operative state of assembly factors.